Reactivity of vanadium oxytrichloride with β-diketones and diesters as precursors for vanadium nitride and carbide. (15th October 2016) - Blackburn, Ben J.; Crane, Jared H.; Knapp, Caroline E.; Powell, Michael J.; Marchand, Peter; Pugh, David; Bear, Joseph C.; Parkin, Ivan P.; Carmalt, Claire J.
Abstract: Vanadium(V) oxytrichloride was reacted with 2, 4-pentanedione, diethyl malonate, and diethyl succinate under inert conditions, forming compounds: dichloro(oxo)(2, 4-pentanedione) vanadium(V) [1 ], dichloro(oxo)(diethyl malonate) vanadium(IV) [2 ] and dichloro(oxo)(diethyl succinate) vanadium(IV) [3 ]. Compounds1 –3 are coordinated to the vanadium centre through the two carbonyl oxygen atoms of the bidentate ligand. It was determined by X-ray crystallography that the structures of the resulting complexes were significantly different, resulting in a monomeric complex (1 ), a tetrameric ring (2 ) and a 1D coordination polymer (3 ). Following the synthesis and isolation of1 –3, they were tested as precursors for vanadium nitride and vanadium carbide by annealing under nitrogen and argon respectively at 1200 °C for 24 h. The resulting materials were characterised by: XRD, EDS, XPS and TEM. Graphical abstract: Highlights: The synthesis of vanadium compounds Dichloro(oxo) (2, 4-pentanedione) vanadium(V), Dichloro(oxo) (diethyl malonate) vanadium(IV) and Dichloro(oxo) (2, 4-pentanedione) vanadium(V) are reported The compounds were evaluated as single source precursors for vanadium nitride and carbide. The synthesis of vanadium nitride or carbide could be effected by altering the gas under which these compounds were annealed at 1200 °C from nitrogen to argon. Dichloro(oxo) (diethyl malonate) vanadium(IV) produced phase pure vanadium nitride and carbide.